(untitled) (Archives of Criminology, 2023)
The Romanian prison system faces several systemic problems such as overcrowding, inadequate conditions of detention, a shortage of staff, especially medical and holding unit guards, and the high frequency of deaths. In many cases, prisoners have complained about infringement of their rights to the European Court of Human Rights, which has repeatedly ordered the Romanian State to pay them compensation. Compensation was significant, and the amounts paid by the Romanian state in the period 2013–2017 total around 5 million euros. Given that the implementation of substantial reforms to help improve detention conditions kept being postponed, in 2017 the ECHR issued a pilot decision (Rezmiveş et al. vs. Romania) suspending prosecution of approximately 8,000 outstanding cases concerning detention conditions, calling on the state to take measures to reduce overcrowding and improve detention conditions. In this respect, a period of six months was granted, during which the Romanian government was to present a plan for the implementation of measures aimed at achieving these objectives. In the short term, the Ministry of Justice and the National Administration of Penitentiaries introduced a compensatory measure which consisted of reducing the total sentence by 6 days for each 30 days executed under improper conditions, the aim being to speed up the process of releasing of prisoners and, therefore, to reduce overcrowding. The law by which the compensatory measure was introduced became the subject of heated debates in Romanian society, with print and online media campaigns being triggered, where this measure was presented as one that “keeps offenders out of prison”, often highlighting cases of former prisoners who had benefited from the provisions of this law and then reoffended. Nevertheless, the non-existent post-detention support given to former prisoners by the Romanian State needs to be taken into consideration. The reaction of the political class was to repeal the normative act, without any alternative measures being implemented. The article aims to carry out an analysis of the realism of these measures, of the context that caused these measures to be taken, and of the debates that existed in society and among the political class, underlining the specific elements of penal populism. The impact of these measures on the prison system will also be analysed.